2015
DOI: 10.1016/j.jmmm.2015.05.087
|View full text |Cite
|
Sign up to set email alerts
|

The effect of magnetic stimulation on the osteogenic and chondrogenic differentiation of human stem cells derived from the adipose tissue (hASCs)

Abstract: a b s t r a c tThe use of magnetic nanoparticles (MNPs) towards the musculoskeletal tissues has been the focus of many studies, regarding MNPs ability to promote and direct cellular stimulation and orient tissue responses. This is thought to be mainly achieved by mechano-responsive pathways, which can induce changes in cell behavior, including the processes of proliferation and differentiation, in response to external mechanical stimuli. Thus, the application of MNP-based strategies in tissue engineering may h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 33 publications
1
22
0
Order By: Relevance
“…Jeong et al found that low-dose ultraviolet B (UVB) radiation did not affect ASC proliferation, while high-dose UVB reduced the proliferation of ASCs [ 79 ]. In addition, many researches showed that magnetism could enhance ASC differentiation, while its ability to enhance ASC proliferation was not confirmed [ 80 , 81 ].…”
Section: Asc's Growth and Differentiation On Biofabricated 3d Scafmentioning
confidence: 99%
“…Jeong et al found that low-dose ultraviolet B (UVB) radiation did not affect ASC proliferation, while high-dose UVB reduced the proliferation of ASCs [ 79 ]. In addition, many researches showed that magnetism could enhance ASC differentiation, while its ability to enhance ASC proliferation was not confirmed [ 80 , 81 ].…”
Section: Asc's Growth and Differentiation On Biofabricated 3d Scafmentioning
confidence: 99%
“…Establishment of spheroids (Emmert et al, 2013;Kapur et al, 2012) or cell seeding on posts using two-dimensional (2D) micro-engineering (Li and Kilian, 2015) may also act as appropriate strategies. Furthermore, applying dynamic conditions such as perfusion (Heo et al, 2016), mechanical (Xu et al, 2015) or magnetic stimulation (Lima et al, 2015) may improve differentiation toward the desired cell type. Finally, material characteristics such as www.ecmjournal.org composition (Lee et al, 2016), surface properties, architectural features (Li and Kilian, 2015), pore size and pore connectivity (Viswanathan et al, 2015) are cues for stem cell differentiation into a certain cell type.…”
Section: Introductionmentioning
confidence: 99%
“…Magnetic platforms have emerged as a technological and versatile field of research to improve cell‐based therapies and tissue engineering and regenerative medicine approaches enabling the design of non‐invasive and remote‐actuated systems to trigger and modulate physiological processes, stimulating healing, and regeneration. The clinical potential of magnetic stimulation is enormous.…”
mentioning
confidence: 99%